A Survey on Food Waste Management System - et. al., Vikram R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Food loss or food waste is the food that is not eaten by the consumer. In addition to that bring down food waste in all role of the food organization is an main part of decreasing the environmental conditions of agriculture, by bring down the whole quantity of water, land and other external resources needed to provide the global group. Decreasing the food waste is the major part of global as it makes the food out of dumping ground. It makes profitable sight at the small scale, by reducing household food bills and at the large scale by decreasing throwing away costs for restaurants. By properly analyzeand manage the food waste makes our world to economically and environmentally healthy and make the resources available for the future generations. Everyday many students in the college wasting lots of foods. So we take an initiative to develop a web application for college used to keep track and analyze the food waste and to take a better decision by knowing what went wrong and to take the essential steps to avoid the food wastage. We planned our web application to have a login form and registration form. The dashboard has a add recipe form and remove recipe form and for wastage entries we have food waste entry form, cook waste entry form and cook item waste entry form. Our web application provides the user to generate analyzed data in table and chart format. The extra cooked recipe can be collected by the nearest Orphanages who actually requested for the food and the food waste and cook waste both were given to the agricultural land for fertilization